Effects of Pig Manure and Cow Biourine Dosage on Growth and Yield of Tomato Plants (Solanum Lycopercium L.) - I Putu Arta Subagia Yasa; Luh Kartini; Ida Bagus Komang Mahardika (SEAS (Sustainable Environment Agricultural Science), 2019)
This study aims to determine the effect of pig manure and cow biourine manure fertilizer on growth on the growth and yield of tomato plants and their interactions. The study was carried out in the Serampingan Village, Selemadeg Sub-district, Tabanan. The study was conducted from May 28 to August 28, 2016. The study made use of Randomized-group Design with 2 factors, consisting of 4 level of treatment, each of which was repeated 3 times so that there were 16 treatment combinations obtained. In this experiment 48 polybags were needed. The results show that the treatment of a dose of pig manure 10 tons/ha (P1) gives the highest yield on the fresh weight of fruit harvested per plant that is 895.83 grams with an increase of 7.39% compared to that of pig manure {30 tons/ha (P3)}, which is only 834.17 grams. At the fresh weight of fruit harvested per plant, the highest interaction of pig manure and biourine was obtained in the treatment (P3B1) of 930 grams which increased by 27.39% compared to the lowest in the treatment (K3B3), which was only 730 grams.